RESEARCH OF THE BAKERY SAFETY CHARACTERISTICS OF QUALITY BREAD FROM LOCAL WHEAT FLOUR MIXTURES (Bulletin of Innovative Research, 2026)
The article shows that samples of grain grown in the Republic, affected by the turtle bug to varying degrees, were studied. It was revealed that the hot climate of grain growing affected changes in flour, the state of the carbohydrate-amylase complex and the weakened activity of amylolytic enzymes.